Durações: a construção de um corpo em performance através da repetição e do tempo - Alcino, Daniel Noronha de (2016)
DURATIONS - Construction of a body in performance through repetition and time is a research-Visual Poetry, in which I study my creative process in drawing up an artwork about performance. This study aims to emphasize possible states \"body-mind\", which allow me as an artist, to build a body in a state of performance using repetition and time duration as triggers and drivers of the process. Methodologically the research is focused on the creative process together with the study of theoretical and artistic references related to the subject and object of study in question: the process of creation in performance, repetition and duration as guiding the procedural dynamics. From the experiments carried out in the studio, I create a kind of cartography for my subject matter (the state of performance) consisting of path: resistant body, powerful body, body territorialized, body in transit and body at rest. This path is explored jointly to the four performances I ve built: DURAÇÃO 1 Resistência, DURAÇÃO 2 Potência, DURAÇÃO 3 Territórios e DURAÇÃO 4 Lentidão. For understanding the body in performance it contemplates another body condition than the everyday; so, I think there is a conscience formed from microperceptions and microspacialities, which allow me to immerge in another spatial dimension and not quantifiable time, space-time performance. By José Gil, Renato Ferracini, Gilles Deleuze, Roberto Machado, Peter Pál Pelbart, Alberto Tassinari, among others, I build a reflection on the body-space-time triad, with which I go through the repetition of concepts (as a producer of differences) and duration (as a way of being in time).